Corporate Sector Accounting and Auditing in the Acquis Communautaire : A Building Block of the Internal Market - World Bank (World Bank, Vienna, 2016)
This guide is designed to ensure that a comprehensive overview of the relevant provisions of the acquis communautaire is available to policymakers, regulators, and other stakeholders in countries with a European vocation or those simply wishing to take the European Union (EU) regulatory model into account when devising their own national approaches. This guide outlines and summarizes the EU legislative framework governing corporate sector accounting and auditing. The guide begins by giving a brief history and overview of the EU, its institutions, and legislative processes in section one. In section two, the guide focuses on the development of the internal market, particularly in the areas of financial market integration and company law harmonization. Section three addresses the harmonization of accounting and auditing in the EU. Section four looks at the most pressing accounting and auditing issues for the EU.